Age-related changes in the marmoset gut microbiome - Reveles, Kelly R. (Am J Primatol, 2019)
The gut microbiome is known to play a significant role in human health but its role in aging remains unclear. The objective of this study was to compare the gut microbiome composition between young adult and geriatric nonhuman primates (marmosets) as a model of human health and disease. Stool samples were collected from geriatric (8+ years) and young adult males (2–5 years). Stool 16s rRNA V4 sequences were amplified and sequenced on the Illumina MiSeq platform. Sequences were clustered into operational taxonomic units and classified via mothur’s Bayesian classifier referenced against the Greengenes database. A total of 10 young adult and 10 geriatric marmosets were included. Geriatric marmosets had a lower mean Shannon diversity compared to young marmosets (3.15 vs. 3.46; p=0.0191). Geriatric marmosets had a significantly higher mean abundance of Proteobacteria (0.22 vs. 0.09; p=0.0233) and lower abundance of Firmicutes (0.15 vs. 0.19; p=0.0032) compared to young marmosets. Geriatric marmosets had a significantly higher abundance of Succinivibrionaceae (0.16 vs. 0.01; p=0.0191) and lower abundance of Porphyromonadaceae (0.07 vs. 0.11; p=0.0494). In summary, geriatric marmosets had significantly altered microbiome diversity and composition compared to young adult marmosets. Further studies are needed to test microbiome-targeted therapies to improve healthspan and lifespan.